Physiological mechanism of lodging resistance of oat stalk and analysis of transcriptome differences - Yu, Jiangdi; Zhang, Ran; Ma, Xiang; Jia, Zhifeng; Li, Xiaoxia; Li, Yuzhu; Liu, Huan (Frontiers in Plant Science, 2025)
IntroductionLodging has become an important factor limiting oats production.MethodsTo understand the relationship between oat lodging and stem growth, we selected three oat cultivars with different lodging resistance traits and conducted a detailed analysis of their stem physicochemical properties, and transcriptome sequencing on them at different growth stages were performed.ResultsImportant plant characteristics like: length of the second stem internode, stem wall thickness, breaking force, mechanical strength, soluble sugar, starch, lignin, and silicon content were closely related to oat lodging performance. With the growth of the second stem internode at the base of oats, the number of coexpressed differentially expressed genes (DEGs) increased. And DEGs were specifically enriched in starch and sucrose metabolism, phenylpropanoidbiosynthesis, MAPK signaling pathway-plant and carbon metabolism. There were many TF family types among the different comparison groups, and p450, Myb_DNA-binding, WRKY, and AP2 families accounted for the most. Additionally, there was a specific high expression of genes related to the synthesis of cellulose(CesA9, CesA7, and CesA4) and lignin (CCR1, 4CL8, and 4CL3) in lodgingresistant cultivar and middle lodging-resistant cultivar. WGCNA analysis identified genes closely related to lodging resistance, namely MBF1c, SKP1, and CAND1, which were specifically up-regulated on the 35th day of growth in the second stem internode of the highly resistant ‘LENA’. These genes can all serve as positive regulatory factors for oat lodging.DiscussionUltimately, our work analyzed the transcriptional network regulatory relationships, laying the foundation for elucidating the physiological and genetic mechanisms of oat lodging resistance, and providing excellent genetic resources for oat and other crop breeding.